1987
DOI: 10.1093/schbul/13.3.395
|View full text |Cite
|
Sign up to set email alerts
|

Infant Predictors of the Longitudinal Course of Schizophrenic Development

Abstract: This study was begun in 1952 to test the hypothesis that specific neurointegrative disorders in infancy predict vulnerability to later schizophrenia and schizotypal disorder. Twelve offspring of chronic schizophrenic mothers and 12 controls from similar low socioeconomic status (SES) backgrounds have been studied since their births in 1952-53 and 1959-60. The infants were ranked according to the severity of their neurointegrative disorder, or "pandysmaturation" (PDM), based on analysis of Gesell tests and phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
1
4

Year Published

1992
1992
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(95 citation statements)
references
References 32 publications
4
86
1
4
Order By: Relevance
“…Consistent with the results of numerous prior studies of children at elevated genetic risk for schizophrenia (Mednick and Schulsinger 1968;Landau et al 1972;Asamow et al 1978;Rutschmann et al 1980;Harvey et al 1981;Winters et al 1981;Worland et al 1982;Driscoll 1984;Lifshitz et al 1985;Sohlberg 1985;Hallett et al 1986;Fish 1987;Goodman 1987;Sameroff et al 1987;Weintraub 1987;Erlenmeyer-Kimling et al 1989;Schreiber et al 1992;Marcus et al 1993;Bergman and Walker 1995), in this study cognitive deficits were also observed among the unaffected siblings of preschizophrenia patients at 4 and 7 years of age, regardless of whether siblings with adult psychiatric disorders were included. Given that a substantial number of the first degree relatives of schizophrenia patients carry a predisposing genotype without manifesting the disorder phenotypically (Fisher 1973;Gottesman and Bertelsen 1989), this pattern is consistent with an association between presence of a genetic diathesis to schizophrenia and expression of cognitive dysfunction during childhood.…”
Section: Childhood Cognitive Dysfunction In Schizophreniasupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with the results of numerous prior studies of children at elevated genetic risk for schizophrenia (Mednick and Schulsinger 1968;Landau et al 1972;Asamow et al 1978;Rutschmann et al 1980;Harvey et al 1981;Winters et al 1981;Worland et al 1982;Driscoll 1984;Lifshitz et al 1985;Sohlberg 1985;Hallett et al 1986;Fish 1987;Goodman 1987;Sameroff et al 1987;Weintraub 1987;Erlenmeyer-Kimling et al 1989;Schreiber et al 1992;Marcus et al 1993;Bergman and Walker 1995), in this study cognitive deficits were also observed among the unaffected siblings of preschizophrenia patients at 4 and 7 years of age, regardless of whether siblings with adult psychiatric disorders were included. Given that a substantial number of the first degree relatives of schizophrenia patients carry a predisposing genotype without manifesting the disorder phenotypically (Fisher 1973;Gottesman and Bertelsen 1989), this pattern is consistent with an association between presence of a genetic diathesis to schizophrenia and expression of cognitive dysfunction during childhood.…”
Section: Childhood Cognitive Dysfunction In Schizophreniasupporting
confidence: 90%
“…Prospective examination of cognitive functioning in individuals who develop schizophrenia as adults provides an indirect means to address these questions. Longitudinal "high-risk" studies have consistently reported that children of patients with schizophrenia perform more poorly on neuropsychological tests than children of other people (Mednick and Schulsinger 1968;Landau et al 1972;Asarnow et al 1978;Rutschmann et al 1980;Harvey et al 1981;Winters et al 1981;Worland et al 1982;Driscoll 1984;Lifshitz et al 1985;Sohlberg 1985;Hallett et al 1986;Fish 1987;Goodman 1987;Sameroff et al 1987;Weintraub 1987;Erlenmeyer-Kimling et al 1989;Schreiber et al 1992;Marcus et al 1993;Bergman and Walker 1995). These findings suggest that early signs of brain compromise in preschizophrenia subjects may be mediated at least in part by genetic predisposition to the disorder.…”
mentioning
confidence: 99%
“…This explanation is supported by evidence from high-risk studies showing that children at genetic risk for schizophrenia are distinguished by impairments of motor development and fine motor coordination, [36][37][38][39][40][41][42][43] which appear to predict schizophreniaspectrum disorders in adulthood. 39,43 Further evidence comes from general population birth cohort studies that show delayed motor milestones, 5 clumsiness, 6 and poor sports ability 44 in childhood as predictors of later schizophrenia, and from studies of childhood home-movie footage of schizophrenic patients showing left-sided neuromotor abnormalities during the first 2 years of life. 45,46 Such abnormalities are not confined to childhood: 33% to 60% of schizophrenic patients, [47][48][49][50][51][52] including neuroleptic-naive patients, 53,54 show "soft" neurological signs in adulthood.…”
Section: Commentmentioning
confidence: 93%
“…En esta linea, Fish (1987) intentó verificar la hipótesis de la «pandysmatura-tion» comparando a doce hijos de madre esquizofrénica con doce controles. Hipotetizó que la pandismaduración o déficit neurointegrativo puede ser marcador infantil de un rasgo esquizotípico inherente.…”
Section: Precursores Ambientales: Familia Y Actitudes Paténtalesunclassified